THE IMPACT OF INDONESIAN PRESIDENTIAL ELECTION THE 2019 ON ABNORMAL RETURN AND STOCK TRADING VOLUME ACTIVITY ON IDX (EMPIRIST EVENT STUDY ON STOCK LISTED IN THE LQ 45 INDEX IN 2019) - Ahmad Amrulah Arif; Sudjono Sudjono (Dinasti Publisher, 2021)
Political events can affect stock prices in economic or non-economic terms. The political events of the general election are quite interesting topics for testing the information content of stock prices on the IDX which is intended to measure market response using abnormal returns, average abnormal returns and trading volume activity as well as average trading volume activity. The purpose of this research is to be able to prove the difference between abnormal return, average abnormal return and trading volume activity as well as average trading volume activity after and before the 2019 Indonesian presidential election. The population of this study is the index published by the IDX and the sample in this study is 45 companies listed in the LQ 45 index. The type of research conducted is quantitative research and secondary data in this study were obtained from the Indonesia Stock Exchange (IDX) and Yahoo Finance. Analysis of the test data using the normality Kolmogrov-Smirnov test and the Ranking Test Wilcoxon because the observation time in the test is 7 days after and 7 days before the 2019 Indonesian presidential election. 2019 there is no significant difference to the average abnormal return and average trading volume activity.